Efektivitas Terapi Musik terhadap Kecemasan Praoperasi pada Pasien dengan Anestesi Spinal - Muhammad Aviv Pasa; Ani Haryani; Qodri Qodri (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Preoperative anxiety is a common emotional response experienced by patients prior to undergoing surgery and may negatively affect physiological stability, anesthetic effectiveness, and postoperative recovery. While pharmacological approaches are often used to manage anxiety, they carry the risk of side effects. Music therapy, as a non-pharmacological intervention, is considered safe, practical, and effective in reducing anxiety. This study aimed to determine the effect of music therapy on the level of preoperative anxiety in patients undergoing spinal anesthesia at RS X. The study used a quasi-experimental design with a pretest-posttest approach and no control group, involving 30 respondents selected by purposive sampling. The results showed a significant reduction in anxiety levels after the intervention, with a Wilcoxon test value of p = 0.000 (p < 0.05). Therefore, music therapy can be considered an effective non-pharmacological intervention to reduce preoperative anxiety.